ANALISIS PLURALISME MASYARAKAT NGGERUKOPA: (Studi Kasus dalam Merawat Kerukunan Beragama) - Haryanto, Lutfin; Atmaja, Jessy Parmawati; Oya, Abas; Haris, Abdul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Pluralism is a view of life in understanding, acknowledging and accepting the existence of pluralism and diversity in a community group. The people of Donggo, Bima Regency, West Nusa Tenggara have different religious beliefs, in which there are different cultures and customs. There are three religions that developed in Palama Village 2, Nggerukopa hamlet, Donggo District, namely Islam, Catholicism and Protestantism. With a variety of religious beliefs, of course, each individual community has different desires, and this can lead to conflict between individuals in the community, for this reason it is necessary to understand pluralism which refers to the meaning of tolerance in order to live in harmony, to unite the diversity of a nation. The formulation of the problem raised in this study is what is the meaning and function of religious harmony in the Nggerukopa community? The purpose of this study is to identify the pluralism of the Nggerukopa community in maintaining religious harmony. Researchers obtain data in this study is from observation, interviews and documentation. The data were analyzed by qualitative descriptive method. Based on the results of the study, it was found that the meaning and function of the harmony of the Nggerukopa community in maintaining religious harmony were understanding each other's feelings in the form of cua kaco'i angi (mutual respect), interacting socially of doho kaboro weki (sitting together), participating in mutual cooperation of n inga dasa uma (helping to build a house), caring for each other of batu rawi rasa (participating in events) and bringing all individuals together in tio kasama weki rasa ra dana (guarding together villages and villages). The researcher concludes that Nggerukopa comunity really care for their religious harmony by understanding the meaning and function of this form of harmony as the basis for living in harmony with one another.